Μια ασυνήθιστη παράσταση επιτάφιου θρήνου από την Αντιόχεια Πισιδίας - Γκιολές, Νίκος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1995)
A short archaeological guide of Antioch in Pisidia features a small late Byzantine crystal pendant icon with an unasual representation of the Lamentation. The scene was influenced by the iconographie subject of Saint-Mandydion in combination with the popular occidental iconographie scene of the Pietà.